Incidencia de los términos de intercambio en las exportaciones en el Perú: 1991-2014 - Valverde Valverde, Eberth (2015)
The research aims to determine the incidence of the terms of trade in exports of Peru during the periodo1991 - 2014, as it is very important to know that magnitude affect the terms of trade l behavior of Peruvian exports. For the development of this work has been compiled data from statistical reports of the Central Reserve Bank of Peru and the National Institute of Statistics and Information, then graphics that allow us to observe the evolution of the terms of trade and exports both traditional was developed and nontraditional finally the econometric model was estimated to determine the extent of the impact of the terms of trade in exports. The research concludes that the impact of the terms of trade in exports in Peru during the period 1991 to 2014 has had a direct relationship, so it is necessary to diversify production to not be so exposed to the negative factors of which the terms of trade, when they reduce effects generated by the international economy.